Muscle-strengthening exercise and positive mental health in children and adolescents: An urban survey study - Zhang, Xiaohui; Jiang, Chujuan; Zhang, Xiaocong; Chi, Xinli (Frontiers in Psychology, 2022)
Background: Much evidence has indicated that physical activity is associated with mental health benefits, such as fewer depression symptoms. Yet, there are few studies examining the association between muscle-strengthening exercise (MSE) with mental health outcomes, especially positive outcomes (e.g., subjective wellbeing). The study aimed to test the association between MSE with subjective wellbeing and resilience among a large sample of Chinese adolescents. Methods: A cross-sectional study was conducted among primary and middle school students in Shenzhen, China. MSE frequency, subjective wellbeing, and resilience were measured. Data from a total of 67,281 adolescents aged 10-17 years (51.9% males and 48.1% females) were included in the analysis. Mixed effect models were performed to assess how weekly MSE frequency (0-7days) related to the levels of subjective wellbeing and resilience, adjusting for potential confounding variables (e.g., sex, grade). Sensitivity analyses were also conducted. Results: Compared to participants with no MSE, the levels of subjective wellbeing were higher in those with higher MSE frequencies (range of β: 0.29 [1 day per week] to 1.98 [7 days per week]). The frequency of MSE was also positively correlated to better resilience (range of β: 0.50 [1 day per week] to 4.40 [7 days per week]). All associations remained significant in sensitivity analyses. Conclusions: More frequent MSE was associated with superior subjective well-being and resilience of Chinese adolescents. Increasing MSE may be beneficial for promoting positive mental health outcomes among adolescents.